Prisão domiciliar: um direito da mãe ou da criança à luz do STF na decisão cautelar do habeas corpus coletivo 143.641- SP/2018? - Lima, Renata Miranda (2020)
The collective habeas corpus 143-641 / SP, was a legal instrument that installed the debate in the Federal Supreme Court regarding jails and violations of the rights of thousands of children and mothers throughout Brazil. The importance of this debate in the Supreme Court goes beyond the material solution of transforming provisional prisons into domiciliary, because with the decision a new collective constitutional remedy capable of protecting wide, massive and systematic violations of the right to liberty was inaugurated. The reception of habeas corpus gains special importance in contemporary times due to the increase of the female prison population. Such an increase raises several problems. The first concerns prison architecture that was not designed for women, which implies several rights violations. The other problem is that incarcerating them reaches, beyond them, their offspring hurting the rights of children enshrined in the Constitution and the Statute of Children and Adolescents. Faced with this situation, the Code of Criminal Procedure extended the modalities of house arrest to mothers of children under 12 years old or to pregnant women, provided that certain legal requirements provided for in articles 318, 318-A, 318-B and 319 of the CPP. However, the legal provision was not enough for its realization, hence the importance of the collective habeas corpus. It is at this juncture that the present dissertation will be developed, which will aim to understand which arguments are used in the votes and which is the right subject recognized to grant the order. Therefore, the hypothetical-deductive method is used, based on bibliographic and documentary research.